Antibiotic Sensitivity Patterns and Molecular Typing of Shigella sonnei Strains Using ERIC-PCR. - Reza Ranjbar; Farzaneh Mirsaeed Ghazi (Tehran University of Medical Sciences, 2013)
Shigella sonnei is considered as a major cause of diarrheal disease in both developing and developed countries. Iran is one of the endemic areas of shigellosis. The present study was undertaken to investigate the antibiotic susceptibility and genetic relatedness of S. sonnei strains isolated from pediatric patients in Tehran, Iran.The study included all S. sonnei strains isolated from pediatric patients with diarrhea admitted to several hospitals in Tehran, Iran, during 2008-2010. Shigella spp. strains were recovered from patients using standard microbiological methods. S. sonnei strains were further studied by antimicrobial susceptibility testing and Enterobacterial Repetitive Intergenic Consensus (ERIC) - PCR analysis.Eighty nine Shigella isolates were isolated. S. sonnei was themost prevalent Shigella species (60.7%) followed by, S. flexneri (31.5%). Eleven antimicrobial resistance patterns (R1-R11) were identified among S. sonnei isolates. The majority of the strains were resistant to trimethoprim-sulfamethoxazole, tetracycline and streptomycin. All isolates were susceptible to ciprofloxacin, ceftizoxime and chloramphenicol. All strains were typable by ERIC-PCR. Five ERIC-PCR patterns (E1-E5) were found among S. sonnei isolates; however the half of the isolates was clustered in E4 pattern.The antibiotic resistance rates are increasing among S. sonnei strains. Moreover, a predominant clone or limited clones of S. sonnei were responsible for shigellosis caused by this Shigella species in pediatric patients in Tehran, Iran.